Optimistic Bias in Time and Cost Estimation for Solar Power Plant Project - Utomo, Bagus Wahyu (SENATIK STT Adisutjipto, 2018)
Industrial environment has seen from the ability of company to meet the high requirements and expectations from consumers on quality, cost, and processing time. Experienced estimators on project tend to underestimate or pesimistic bias when assessing when project will be completed or how much it will cost for the project. Purpose of this study is to identify whether optimistic biases influence project estimation and submit proposal intervention. This study use a solar power plant project as a case study. Respondents in this study were employees of an EPC company that was categorized as a novice and expert. Optimistic bias occur on the accuracy of time and the cost of the respondent. In general, the accuracy of expert respondents in estimating project time and costs is more accurate than respondent novice. Intervention in this study is when estimating project time and costs should be carried out by expert category estimator.